(untitled) (INNOVATIVE ECONOMY, 2020)
Demchyshak N.B., Hlutkovskyy M.O. DEVELOPMENT OF DIGITAL ECONOMY IN UKRAINE: CONCEPTUAL BASES, PRIORITIES AND ROLE OF INNOVATIONS Purpose. The aim of the article is deepening the conceptual understanding of the digital economy and substantiation of digitalization priorities in Ukraine. Methodology of research. General scientific and special methods are used in the process of research, in particular: analysis and synthesis ‒ to reveal the economic essence of digitalization of the economy; statistical and graphic methods ‒ in the analysis of world trends in the development of information and communication technologies; methods of induction and deduction, abstract and logical method ‒ in substantiating the conclusions of the study. Findings. It is established that the digital economy as a new modern type (model of development of the economy) already includes the essential characteristics of the innovation economy and the knowledge economy. It is argued that high-tech production, innovative nature and modernization of industrial sectors based on information and communication and digital technologies, the dynamics of digital transformations for Ukraine should be a priority solution to achieve sustainable economic growth and development. The priorities of digitalization in Ukraine are substantiated. It is proved that the need for scientific and technological research, the formation of a certain business (digital) culture, the implementation of the ideas of so-called smart cities based on the development of local communities and the emergence of new initiatives and proposals for innovative solutions. Originality. The conceptual understanding of the digital economy is deepened and it is proposed to consider it as a new type of economy, the functioning of which is accompanied by the predominant provision of a variety of services and online products and innovative solutions in finance, manufacturing and social sphere. Practical value. The obtained results of the study should contribute to the formation of the institutional basis for further development of innovative technologies in Ukraine, their introduction into the real sector of the economy, as well as in the future – building an effective digital economy focused on innovation in production and services. Key words: digital economy, innovations, digital services, concept, digitalization.